Developing an English Summative Computer-Based Test (CBT) for Tenth Grade Students - Machtowil, Putro Bagus Wahida; Tresnadewi, Sintha; Ivone, Francisca Maria (Jurnal Pendidikan: Teori, Penelitian, dan Pengembangan, 2023)
The use of ICT in language testing has recently expanded to more diverse computer-based exams. This includes achievement test like UNBK (Ujian Nasional Berbasis Komputer) and university entrance test such as SBMPTN (Seleksi Nasional Masuk Perguruan Tinggi Negeri). thus, students need to get used to using this kind of test before taking a competency exam. The method employed in this study is Research and Development (R&D). Based on the process and results of the development of this English Computer Based Test, it has many features that can cover the difficulties in conducting online tests such as timers, anti-cheating, and other features that are always a challenge in online tests. Some features are not working normally like audio and also some bugs in the product. Furthermore, these products can provide insight into the effectiveness of online tests and can be adjusted to the needs of test makers.